The family guide to Bath : souvenir poster, free postcards and 4 city walks with maps - Phipps, Rosemary (Andover : Pitkin Pictorials)
Plan of the Roman baths - The legend of Bladud - The Romans arrive - The building of the Temple - The development of the Bath complex - Gods and Goddesses